2021
DOI: 10.1002/aqc.3632
|View full text |Cite
|
Sign up to set email alerts
|

Colonization history and human translocations explain the population genetic structure of the noble crayfish (Astacus astacus) in Fennoscandia: Implications for the management of a critically endangered species

Abstract: 1. The noble crayfish (Astacus astacus) is an endangered freshwater species in Europe. The main threat is from lethal crayfish plague, caused by the oomycete Aphanomyces astaci that has been spread over Europe by introduced North American crayfish species, acting as chronic carriers of the disease.2. Most of the remaining noble crayfish populations are found in the Baltic Sea area, and there is an urgent need to implement conservation actions to slow down or halt the extinction rate in this region. However, li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…In the same way, claims have been made that A. astacus was introduced into Sweden during the 1500s by the kings. Later genetic studies have shown that A. astacus has inhabited Swedish aquatic ecosystems since the last ice age, thus being native to Sweden (Edsman et al, 2002;Gross et al, 2013;Dannewitz et al, 2021). Similarly, A. pallipes has been claimed to have been introduced to Spain from Italy only in the 1500s (Clavero et al, 2016), despite genetic evidence dating the species origin on the Iberian Peninsula from the last glaciation (Matallanas et al, 2011(Matallanas et al, , 2016Jelić et al, 2016;Martín-Torrijos et al, 2021a).…”
Section: Twisting the Definitions And Creating New Language To Cause Confusionmentioning
confidence: 99%
“…In the same way, claims have been made that A. astacus was introduced into Sweden during the 1500s by the kings. Later genetic studies have shown that A. astacus has inhabited Swedish aquatic ecosystems since the last ice age, thus being native to Sweden (Edsman et al, 2002;Gross et al, 2013;Dannewitz et al, 2021). Similarly, A. pallipes has been claimed to have been introduced to Spain from Italy only in the 1500s (Clavero et al, 2016), despite genetic evidence dating the species origin on the Iberian Peninsula from the last glaciation (Matallanas et al, 2011(Matallanas et al, , 2016Jelić et al, 2016;Martín-Torrijos et al, 2021a).…”
Section: Twisting the Definitions And Creating New Language To Cause Confusionmentioning
confidence: 99%
“…Fragmentation was proved to be one of the main issues in the long run of protecting sensitive species, even in the context of protected areas that may offer appropriate local conditions but failed in ensuring connectivity between populations [31]. Probably one of the most impacting phenomena, the dominance of invasive alien species [32][33][34][35][36][37], accompanied by the carried deadly disease known as crayfish plague [38][39][40], led to dramatic changes in the distributions of European indigenous crayfish species in the last decades [38]. Modern conservation actions should consider an extensive array of factors that should be monitored and controlled.…”
Section: Introductionmentioning
confidence: 99%
“…The authors suggest that current conservation and management programs should consider three phylogeographic groups as essential management units in order to preserve the remaining genetic diversity, which is critically threatened by crayfish plague (Martín-Torrijos et al, 2019). It has been shown for many crayfish species that there are significant differences regarding the genetic diversity across Europe, and that restocking programs should always consider the natural genetic make-up of the populations (e.g., Schrimpf et al, 2014Schrimpf et al, , 2017Lovrenčić et al, 2020;Dannewitz et al, 2021). For restocking purposes, conservationists rely on efficient crayfish breeding systems.…”
Section: Crayfish Management and Re-introductionsmentioning
confidence: 99%